KONSEPSI PEMIKIRAN DASAR EKONOMI ISLAM, EKONOMI PANCASILA DAN EKONOMI KERAKYATAN UNTUK KESEJAHTERAAN MASYARAKAT - Alvien Septian Haerisma (Al-Mustashfa: Jurnal Penelitian Hukum Ekonomi Syariah, 2019)
AbstractNormatively, religious teachings can influence economic activity in the previous economic system. Meanwhile the Islamic economic system is far ahead which inspires the thinking of the two major economic systems, because the Islamic economic system is inspired by the Koran and al-Hadith. Meanwhile, Indonesia prioritizing the unification of the national economy which is characterized by the value of Pancasila and the 1945 Constitution which is based on the value of God. Using the literature study method, this research produced, first, the basic thinking of Islamic economics consisting of monotheism and brotherhood, work and productivity, ownership and equitable distribution. Pancasila economic principles consist of economic, social and moral integration, social equality, nationalistic spirit, cooperation, decentralization, and regional autonomy. The principle of the popular economy consists of the economy compiled the principle of kinship, the livelihood of the people is controlled by the state, all wealth is controlled by the state and used for the prosperity of the people. Second, the equality of the three reflects ethics, norms and morals, equality, nationalistic values, the role of micro institutions, decentralization and regional autonomy. The difference reflects ethics, norms, and morals by the philosophy of the Koran and al-Hadith, creating a prosperous country, prioritizing the value of hablum minallah and hablum minannas.Keywords: Islamic Economics, Pancasila Economics and Kerakyatan Economics.Â AbstrakSecara normatif bahwa ajaran agama dapat memberikan pengaruh terhadap aktivitas ekonomi pada sistem ekonomi sebelumnya. Sementara itu sistem ekonomi Islam jauh lebih dahulu yang memberikan inspirasi pemikiran kedua sistem ekonomi besar tersebut, karena sistem ekonomi Islam diilhami al-Quran dan al-Hadits. Sementara itu, di Indonesia memprioritaskan penyatuan ekonomi nasional yang bercirikan nilai pancasila dan UUD 1945 yang berasaskan nilai ketuhanan. Dengan menggunakan metode studi kepustakaan, penelitian ini menghasilkan, pertama, pemikiran dasar ekonomi Islam terdiri tauhid dan persaudaraan, bekerja dan produktivitas, kepemilikan dan distribusi berkeadilan. Prinsip ekonomi pancasila terdiri penyatuan ekonomi, sosial dan moral, kemerataan sosial, semangat nasionalistik, kerjasama, desentralisasi dan otonomi daerah. Prinsip ekonomi kerakyatan terdiri perekonomian disusun azas kekeluargaan, hajat hidup orang banyak dikuasai oleh negara, segala kekayaan dikuasai oleh negara dan dipergunakan untuk kemakmuran rakyat. Kedua, persamaan ketiganya mencerminkan etika, norma dan moral, kemerataan, nilai nasionalistik, peran lembaga mikro, desentralisasi dan otonomi daerah. Perbedaannya mencerminkan etika, norma dan moral sesuai filosofi al-Quran dan al-Hadits, mewujudkan negara yang makmur, mengedepankan nilai hablum minallah dan hablum minannas.Kata Kunci: Ekonomi Islam, Ekonomi Pancasila dan Ekonomi Kerakyatan.